TENTANG ASPEK STOKASTIK DIFUSI PADA KERAGAMAN BERBOBOT - , NURFARISHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Stochastic process extention has been built for a diffusion on weighted manifolds through stochastic differential equation. Diffusion process extention is done by reformulating weighted Laplasian-Beltrami operator which is functioned as a generator in that process. The result shows that diffusion process in weighted manifolds is little different from diffusion process in Riemanian manifold. It is caused by addition the density function of the measure m. This study also discusses about diffusion process on special object it is torus T2